Oxford studies in ancient philosophy. Volume 42 - Inwood, Brad. (Oxford : Oxford University Press, 2013)
'Oxford Studies in Ancient Philosophy' is a volume of original chapters on all aspects of ancient Greek and Roman philosophy, published twice a year. The series aims to provide the best contemporary work in the field, covering all periods from the Presocratics to the philosophy of late antiquity.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Philosophy, Ancient -- Periodicals